Enhancement of the physical adsorption of some insoluble lead compounds from drinking water onto polylactic acid and graphene oxide using molybdenum disulfide nanoparticles: Theoretical investigation - Mahdhi, Noureddine; Alsaiari, Norah Salem; Amari, Abdelfattah; Osman, Haitham; Hammami, Saber (Frontiers in Physics, 2023)
This study reports the enhancement of the physical adsorption of some insoluble Lead insoluble compounds, from drinking water, onto Polylactic acid (PLA) polymer and graphene oxide (GO) by filling with Molybdenum Disulfide (MoS2) Nanoparticles (NPs) . Based on Lifshitz theory, we demonstrate the attractive nature of the van der Waals (vdW) interactions, that are responsible for the physical adsorption, between the Cerussite (PbCO3), the Pyromorphite (Pb5(PO4)3Cl) and the Lead Dioxide (PbO2) insoluble adsorbates and the GO/MoS2, PLA/MoS2 adsorbents nanocomposites in water medium. Subsequently, we show the increase of the physical adsorption, at close and large separation distance (<100 nm) in water medium, between the Lead insoluble adsorbate and the adsorbent GO/MoS2, PLA/MoS2 nanocomposites by increasing the filling ratios (0 %, 10 %, 20 % and 30 %) of MoS2 NPs. Also, for the each Lead insoluble adsorbate, we demonstrate that the vdW adsorption potential and force were more important for GO/MoS2 than for PLA/MoS2 adsorbent. However, for fixed filling rate, the physical adsorption were more important in the order PbO2 > Pb5(PO4)3Cl > PbCO3. Interestingly, we demonstrate that the physical adsorption was strongly dependent to the GO/MoS2 and PLA/MoS2 adsorbents type and the poorly pendent to the Lead compounds adsorbates. For all ‘PbO2, Pb5(PO4)3Cl and PbCO3’ adsorbates, we demonstrate that the vdW adsorption potential and force were higher ⁓6, ⁓3.1, ⁓2.2 and ⁓1.9 times for GO than for PLA adsorbent for respectively filling ratios 0 %, 10 %, 20 % and 30 % of MoS2 NPs.